YOGA PRACTICE AND BIOCHEMICAL AND PHYSIOLOGICAL ALTERATIONS IN NORMAL SUBJECTS - Sharma, Preeti; Anand, Sharmila; Kumar, Pradeep; Malhotra, Varun; M, Itagappa; Tripathi, Yogesh; Ps, Dhot; Pughazhendhi, Harish Ram; Biswas, Sayanha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To assess the effect of 45 minute yogic kriya (Surya Namaskar and Kapalbhati) for 30 days on various physiological and biochemical parameters. Methods: About 20 Nursing College students of the Santosh Medical University, Ghaziabad, between the age group 17 and 21 years volunteered to participate in the study. They were divided into two Groups A and B. Group A students including 10 students in each group were subjected to 30 days yoge kriya for 45 minutes for 6 days in a week. Statistical analysis: A student's t-test was used for comparing the means of pre- and post-yoga results of various parameters. Results: No significant difference was found in systolic blood pressure, pulse, body mass index, hemoglobin except for fasting blood sugar and diastolic blood pressure (p<0.001) among the yoga subject while comparing with baseline values and control. Keywords: Yoga, Biochemical alterations, Physiological alterations, Surya Namaskar and Kapal Bhati.